THE ANALYSIS OF FORM, INSTALLATION TECHNIQUE, AND MEANING OF SUNTIANG TUSUAK FOR BRIDAL MAKEUP OF MINANGKABAU ETHNIC COMMUNITY IN THE COASTAL AREA OF PADANG - Vivi Efrianova, Ambiyar, Unung Verawardina, Ferdiansyah, Fani Keprila Prima, Junil Adri, Abrar Tanjung (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The traditional suntiang in for bridal makeup of the Minangkabau area ethnic community in the coastal area of Padang bridal make-up is termed sSuntiang tusuak, which has existed since our ancestors and was influenced by Chinese culture. Suntiang Tusuak for the arrangement of the bridal head has become a hereditary tradition that deserves to be preserved, to save knowledge which is a cultural asset that has only been stored in the memory of an aging bridal makeup. This research is a qualitative research, which aims to obtain a description or description of the shape form, installation technique, and food meaning of suntiang tusuak for bridal makeup in the coastal area of Padang bridal make-up. The data was collected by means of observation and direct interviews with research informants, namely including: bridal make-up artists, suntiang craftsmen, bundo kanduang and cultural observers. Informants were determined using the snowball sampling technique. The results of research in the field indicate that the form of suntiang tusuak is generally in the form of a semicircle, which consists of various forms of suntiang tusuak flower decoration ornaments in the form of flora and fauna forms. The technique of fitting installation technique of the suntiang tusuak consists of two parts (1) the technique of fitting installing the bun, (2) the technique of installing various kinds of suntiang tusuak decorations. (3) The meaning contained in suntiang tusuak is based on the mindset and philosophy of the Minangkabau ethnic community, namely "alam takambang jadi gurunature takambang becomes a teacher" and the philosophy of life "adat basandi syarak, syarak basandi Kitabullah" which is are closely related to the social system and the formation of the identity of the bride and groom in order to have good attitudes and behavior in navigating household life in order to get happiness.